Pengaruh Personal Selling, dan Slogan Iklan Terhadap Brand Awareness Produk Yakult - Efendi, Rahayu; Mashadi, Mashadi (Jurnal Ilmiah Manajemen Kesatuan, 2020)
Yakult is the first probiotic drink in Indonesia since 1991. Until now, Yakult is still the number one pioneer of fermented milk drinks in Indonesia. The purpose of this study is to determine the effect of Personal Selling on Brand Awareness, determine the effect of Advertising Slogans on Brand Awareness, and to determine the effect of Personal Selling and Advertising Slogans on Brand Awareness together. This research was conducted with a quantitative descriptive approach with a random sampling method. The number of respondents in the study were 100 respondents who will be analyzed using SPSS 22 software. The statistical method used is multiple linear regression by testing the classical assumptions, correlation coefficients and coefficient of determination, and conducting hypothesis testing (f test and t test). The results showed that Personal Selling did not affect Brand Awareness positively and significantly, while Advertising Slogans affected Brand Awareness positively and significantly. Meanwhile, together with Personal Selling and Advertising Slogans, it affects Brand Awareness. If the personal selling and advertising of a company is getting better, then the potential Brand Awareness of the public towards the company will also increase, conversely if consumers do not have an interest in personal selling or advertising carried out by the company, the potential Brand Awareness owned by consumers will also be low . Keywords: Brand Awareness, Personal Selling, Ad Slogans